Forming The Quality Of Life In Slovakia After Entering The EU - Vieroslava Holková; Matej Valach; Alexandra Veselková (European Scientific Journal, ESJ, 2016)
Quality of life is one of the most frequent notions of today in European space. It is used primarily as a target value of economic development of the society, but has also become a new challenge to ensure a dignified life of EU citizens. Quality of life can be considered as the holistic category, but can be analyzed also as a fragment in the meaning of orientation only in terms of the individual, respectively partial areas (domains) of human life. One of the important components of quality of life is consumption. From a microeconomic perspective consumption not only speaks about the degree of satiation of human needs but its structure and level is an important factor in shaping the quality of life. If the quality of life in terms of consumption is monitored, its existential side is evaluated using three spheres, namely sphere of non-working time, leisure time and crosscutting areas. The present contribution focuses on the analysis of these spheres and assessment of the quality of life of Slovak households after joining the EU in terms of changes in consumption. The aim of this paper is to create a picture of the formation of quality of life after joining the EU, while providing a prediction of possible developments in this area.